Rekonstruksi Konsep Kesiapan Menikah dalam Perspektif Psikologi Pendidikan Islam: Integrasi Kematangan Spiritual, Emosional, dan Sosial Menuju Keluarga Sakinah - Dony Agus Prasetyo; Siti Rokhimah (Lembaga Yasin AlSys, 2026)
The phenomenon of increasing divorce rates, household conflicts, and low readiness among couples in entering married life indicates that readiness for marriage cannot be understood merely as readiness in terms of age, economy, or administration. This study aims to reconstruct the concept of readiness for marriage from the perspective of Islamic Educational Psychology through the integration of spiritual, emotional, and social maturity as the foundation for forming a sakinah family. This study uses a library research method with a qualitative-descriptive approach. Data were obtained from the Qur’an, Hadith, psychology literature, Islamic educational psychology, and previous research findings relevant to readiness for marriage, then analyzed using content analysis techniques to formulate a comprehensive conceptual construction of readiness for marriage. The results of the study show that readiness for marriage from the perspective of Islamic Educational Psychology is a condition of individual maturity that includes three main dimensions, namely spiritual maturity in the form of the quality of faith, piety, and understanding of the purpose of marriage; emotional maturity in the form of the ability to manage emotions, resolve conflicts, and build healthy communication; and social maturity in the form of the ability to carry out family roles, adapt to the social environment, and take responsibility for household life. The integration of these three dimensions produces a more holistic model of readiness for marriage than Western psychological approaches, which tend to be oriented toward individual aspects. The conclusion of the study affirms that readiness for marriage needs to be built through a balance of spiritual, emotional, and social dimensions as the basis for forming a sakinah, mawaddah, wa rahmah family. The implications of this study indicate the importance of strengthening premarital education based on Islamic Educational Psychology as a preventive effort to build family resilience and reduce the risk of household conflict.